Exploring Students' Motivation in Physical Education, Sports and Health : Literature Review Study - Syafri , Muhammad Adib; Fernando, Ricky (Indonesian Journal of Sport Management, 2025)
The purpose of review literature This is For reviewing scientific literature about explore motivation students in education physical sport health. Two databases (Google Scholar) were used For choose articles containing​ information about Motivation Students In Physical Education Health Sports. After the criteria exclusion only 12 articles submitted​ category. The results show type research used​ namely; Descriptive qualitative, survey and correlation. Almost overall study use questionnaire and interview in data collection. Research Exploring Motivation Students In Physical Education Sport Health is shared in four group, ( i ) motivation students in education physical sport health, (ii) study motivation students in education physical sport health, (iii) survey motivation students in education physical sport health, (iv) relationships motivation students in education physical sport health. Some inherent limitations​ in review has noted. First, although thorough literature search a number of published research​ Possible ignored because the keywords are possible different from the one used moment This. Second, the database (Google Scholar) used in search article. Third, search article more from one country, namely Indonesia and England.